2006
DOI: 10.1099/vir.0.81236-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis and phylogenetic relationships between east, central and west African isolates of Yellow fever virus

Abstract: Yellow fever virus (YFV), a reemerging disease agent in Africa and South America, is the prototype member of the genus Flavivirus. Based on examination of the prM/M, E and 39 non-coding regions of the YFV genome, previous studies have identified seven genotypes of YFV, including the Angolan, east/central African and east African genotypes, which are highly divergent from the prototype strain Asibi. In this study, full genome analysis was used to expand upon these genetic relationships as well as on the very li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…The prM/E phylogeny supports the major genotype and subclade distinctions observed previously in phylogenies based on full genome sequences [22], the complete E gene [9], and the 3′ non-coding region [23] . Four key observations can be drawn from the structure of the YFV phylogeny.…”
Section: Resultssupporting
confidence: 81%
“…The prM/E phylogeny supports the major genotype and subclade distinctions observed previously in phylogenies based on full genome sequences [22], the complete E gene [9], and the 3′ non-coding region [23] . Four key observations can be drawn from the structure of the YFV phylogeny.…”
Section: Resultssupporting
confidence: 81%
“…The results indicated that the CNYF01/2016 sequence was most closely related to the YFV strain Angola71 (GenBank NO AY968064), which was isolated in Angola in 1971 13 and the complete genomic sequence was reported in 2006. 14 Both strain CNYF01/2016 from the imported case from Angola in 2016 and strain Angola71 from 1971 shared the same Angola genotype.…”
Section: Resultsmentioning
confidence: 99%
“…A neighbor-joining analysis of African YFV strains, provided evidence for the presence of 5 prototype lineages in circulation in the continent, West Africa I, West Africa II, East Africa, East/Central Africa, and Angola [12]. Subsequent analysis using full-length YFV sequences provided confirmatory evidence for the putative geographic structure [13].…”
Section: Introductionmentioning
confidence: 88%